Epigeic bryophytes of the forest ecosystems, peculiarities of their water exchange and productivity depending on the ecological locality conditions (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Question: What is the species diversity of epigeic bryophytes in the forest ecosystems of the Ukrainian Roztochya? Locations: Ukrainian Roztochya Methods: field study in the plots with certain ecological values Nomenclature: Hodgetts et al. 2020 Results: Differences in their water exchange and productivity have been established depending on locality conditions. A total of 48 species of bryophytes were found in the epigeic communities, of which the largest number (33 species of bryophytes and 2 species of liverworts) is found in the protected area of ancient forests. An increase in the number of xero-morphic ruderal and colonists in forest mesomorphic communities is an indicator of the degree of disruption of forest ecosystems by both natural and anthropogenic factors. More stable conditions of the water regime and higher humidity were determined in bryophytes and in the soil under them in the territory of old beech forests and stands of pine, compared to the areas of stationary recreation. Research results indicate that mosses of forest ecosystems had a fairly high chlorophyll content and low values (1.48–2.17) of Chl a/b ratio, which indicates not only their shade tolerance, but also greater adaptability to a wide range of lighting. For forest dominants of the family Polytrichaceae, the highest indicators of phytomass and photosynthetic productivity were recorded. In ancient forests, the phytomass of these species, depending on locality conditions, reached 337.55–784.57 g/m2, the indicators of the content of Chl a+b ranged from 3.82 to 4.61 mg/g of dry matter mass, СhI – 1.27–7.87 g/m2. Somewhat lower values of phytomass (584.86–784.57 g/m2) were estab-lished for subdominant species of the genus Plagiomnium, the content of of Chl a+b in which was 3.18–3.73 mg/g of dry matter mass, and СhI – 1.86–2.93 g/m2. In the disturbed areas, for small turf synuses of mosses-colonist and thallose-weft synusiae with the participation of liverworts, the above-ground phytomass of assimilating shoots (428.11–726.79 g/m2) and photosynthetic productivity (0.39–0.80 g/m2). Conclusions: Indicators of primary productivity show that the ability of the bryophyte cover to bind atmospheric carbon has an indicative value for assessing the state and functional features of forest ecosystems and depends on the species composition of bryosinuses, their phytomass indi-cators, and the content of chlorophylls in different locality conditions.
Keywords: bryophytes, water-holding capacity, pigment complex, chlorophyll index.